A Longitudinal Investigation of Trauma Exposure, Retraumatization, and Post-Traumatic Stress of Justice-Involved Adolescents (Maricopa County, AZ and Philadelphia County, PA), 2000-2010 - Loughran, Thomas A. ([Verlag nicht ermittelbar], 2019)
This study examined the evolution of exposure to violence and psychological distress among adolescents using a sample of 1,354 male and female youths who completed a baseline assessment and 10 follow-up interviews over a seven-year period as part of the Pathways to Desistence study. Statistical analyses were utilized to identify a taxonomy based on adolescents' patterns of exposure to violence as well as to explore the association between the analytically-identified exposure to violence patterns and various psychological symptoms. Additional models were analyzed to examine changes in exposure to violence over time, changes in psychological distress over time, the contemporaneous, parallel processes of changes in exposure to violence and psychological distress over time, and differences in the evolution of violence exposure and psychological distress across sex and race/ethnicity.